Implication of 99mTc-sum IL-2 SPECT/CT in immunotherapy by imaging of tumor-infiltrating T cells. Issue 3 (1st March 2023) - Gao, Yu; Luo, Qi; Sun, Zhichen; Gao, Hannan; Yu, Yue; Sun, Yining; Ma, Xiaotu; Han, Chuanhui; Shi, Jiyun; Wang, Fan
Abstract : Background: Although immune checkpoint blockade (ICB) and adoptive T cell transfer (ACT) therapy have achieved impressive clinical outcomes, majority of patients do not respond to immunotherapy. Tumor-infiltrating T cells, a critical factor to immunotherapy, is dynamically changing. Therefore, a reliable real-time in vivo imaging system for tumor-infiltrating T cells, but not immunohistochemical analyses, will be more valuable to predict response and guide immunotherapy. In this study, we developed a new SPECT/CT imaging probe 99m Tc-sum IL-2 targeting the IL-2Rβ/IL-2Rγ (CD122/CD132) receptor on tumor-infiltrating T cells, and evaluated its application in predicting the immune response to anti-PD-L1 (αPD-L1) therapy as well as tracking infused T cells in ACT therapy. Methods: The binding affinity of the super mutated IL-2 (sum IL-2) in various T cell subtypes was measured. Sum IL-2 was subsequently labeled with 99m Tc through Sortase-A mediated site-specific transpeptidation. SPECT/CT imaging and biodistribution studies of 99m Tc-sum IL-2 were performed in a MC38 mouse model. Wild type IL-2 (IL-2) was used as control in the above studies. Finally, we evaluated 99m Tc-sum IL-2 SPECT/CT for the detection of tumor-infiltrating T cells in the context of αPD-L1 immunotherapy and ACT therapy. Results: Sum IL-2 preferentially bound to CD8 + T cells, especially activated CD8 + T cells, while IL-2 showed biased binding to Treg cells. As a result, 99m Tc-sum IL-2 could detect tumor-infiltrating T cells. In the MC38 tumor model, SPECT/CT imaging showed the increased tumor uptake of 99m Tc-sum IL-2 after αPD-L1 treatment, suggesting that the treatment significantly increased tumor-infiltrating T cells, resulting in a correspondingly significant curative effect. In addition, 99m Tc-sum IL-2 SPECT/CT could also track the infiltration of antigen-specific cytotoxic CD8 + T cells during ACT therapy. Conclusion: 99m Tc-sum IL-2 has great clinical potential for non-invasive and specific SPECT/CT imaging of tumor-infiltrating T cells as well as for timely prediction and evaluation of the therapeutic efficacy of ICB and ACT therapy.